2014
DOI: 10.1039/c4ra03905j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tumor targetability of PEGylated mesoporous silica nanoparticles on in vivo optical imaging according to their size

Abstract: The 100–150 nm-sized MSNs showed higher uptake at the tumor site in a particle size-dependent in vivo optical imaging study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Hobbs et al demonstrated that particle permeability for orthotopic brain tumors was limited to particles with a diameter ranging from 7 to 100 nm (33); however, differences within the size range were not described. Kim et al reported that PEGylated silica nanoparticle uptake in a U87MG mouse xenograft was greater with 100–150 nm particles as compared with larger and smaller particles (40 and > 300 nm) (38). However, in this study the tumor was implanted in the mouse shoulder, which may differ in the pore cutoff size as compared with the orthotopic brain tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Hobbs et al demonstrated that particle permeability for orthotopic brain tumors was limited to particles with a diameter ranging from 7 to 100 nm (33); however, differences within the size range were not described. Kim et al reported that PEGylated silica nanoparticle uptake in a U87MG mouse xenograft was greater with 100–150 nm particles as compared with larger and smaller particles (40 and > 300 nm) (38). However, in this study the tumor was implanted in the mouse shoulder, which may differ in the pore cutoff size as compared with the orthotopic brain tumor.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the 100–150 nm-sized particles had an 4–6.5 fold higher tumour uptake than the ones with diameter < 30 or >300 nm. 97 Decuzzi et al also studied the MDA-MB-231 breast tumour uptake of spherical silica beads with sizes ranging from 700 nm to 3 μm. 94 They found that the number of beads accumulated in the tumour site increased monotonically as the diameter decreased from 3 μm to 700 nm.…”
Section: Tumour Vascular Abnormalitiesmentioning
confidence: 99%
“…High stability due to the charged surface, easy accomplishment of modification of the surface via siloxane-based cross linkers, and reactants-permeable mesoporous silica structures all make silica based nanoshells for use as biosensors, biomarkers, and other biomedical detectors. For instance, fluorophore-conjugated silica NPs had long been used as optical imaging agents with excellent 76,77 photostability and high fluorescence emission intensity.…”
Section: Biomedical Applications Of Npsmentioning
confidence: 99%
“…To date, silica NPs doped with fluorescent dyes, fluorescent NPs, or QDs were extensively studied as optical imaging probes for various biological [77][78][79][80][81][82] applications such as targeted cancer imaging in vitro and in vivo. For more reading about biomedical applications of silica NPs, please refer 83,84 to several excellent reviews .…”
Section: Biomedical Applications Of Npsmentioning
confidence: 99%